PEMANFAATAN SAMPAH SAYUR PASAR DALAM PRODUKSI LISTRIK MELALUI MICROBIAL FUEL CELLS (UTILIZATION OF MARKET VEGETABLE WASTE IN ELECTRICITY PRODUCTION THROUGH MICROBIAL FUEL CELLS) - Muhamad Imaduddin; - Hermawan; - Hadiyanto (PSTE UNIMUS, 2014)
The presence of organic market vegetable waste is so abundant. One of utilization of vegetable market waste is processed into compost. However, compost has difficulties in marketing so it is only used on a small scale and it gives impact to the environment such as acidification and eutrophication. On the other hand, the threat of energy and fuel-crisis makes activities related to renewable energy into something urgent to be done. One of the renewable energy alternatives is Microbial Fuel Cells (MFCs). MFCs are bioelectrochemical system spontaneously converting biomass into electricity through metabolic activity of microorganisms. The purpose of study is to apply MFCs as an application of voltaic cells in producing electricity using slurry phase of vegetable waste as substrate. Variations performed on the slurry phase comparison: water are 1: 2; 1: 1 and 2: 1, and the addition of EM4. Operations were conducted for 21 days. Production of the greatest voltage is at R1+ reactor (1:2 with addition of EM4) and reached 1180 mV. An electric current is 5.1 μA, and the electric power is 6.02 Mwatt, and the power density is 462.92 mWatt/m2. The presence of water in MFCs role in the mechanism of vegetable waste degradation. The tendency of increase in the electrical energy at the beginning of the operation of the reactor showed an increase in cellular synthesis of microorganisms. Declining electric energy is influenced of pH as microorganisms living place and the formation process of attached media at the electrode. Keywords: Vegetable Market Waste, Electricity, Microbial Fuel Cells.